(untitled) (Journal of Applied and Natural Science, 2015)
In present study, Thermomyces sp. were able to produce high yield of yellow pigments screened. Pigment production by Thermomyces sp was optimized by employing factorial design and response surface techniques in submerged fermentation. The variables evaluated were the concentrations of, sucrose, yeast extract, ammonium sulphate, magnesium sulphate and dipotassium hydrogen phosphate having as response pigment production. One factor at-a-time method was employed for the optimization of media components. Response surface methodology (RSM) optimized these nutrient parameters for maximum yellow pigment production (1387 OD units), which resulted at 35.5 g/L sucrose 5.5 g/L yeast extract, 2.5 g/L NH4SO4, 0.3 g/L MgSO4 and 1.0 g/L K2HPO4 in the medium. Response surface methodology (RSM) was further used to determine the optimum values of process variables for maximum yellow pigment production. The fit of the quadratic model was found to be significant. A significant increase in yellow pigment production was achieved using RSM.